Non-take-up of student financial help: A microsimulation for Germany - Stefanie P. Herber; Michael Kalinowski (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper estimates the percentage of students who do not take up their federal need-based student financial aid entitlements and sheds light on determinants of this behavior. Against the background that educational mobility in Germany is low although extensive student financial aid for needy students is available, it is crucial to know whether students assert their claims for student aid at all. To investigate non-take-up, we set up a microsimulation model for the German Socio-Economic Panel Study 2002-2013 and estimate the respective aid amounts students would have received, had they filed an application for need-based aid. The results indicate that about 40% of the eligible low-income students do not take up their entitlements. We employ instrumental variable techniques and a sample selection model to consider several potential explanatory factors for this behavior. Our results suggest that non-take-up is inversely related to the level of benefits, though the elasticity is rather low. Apart from that, a shorter expected duration of benefit receipt is related to a higher non-take-up rate, whereas the possibility to draw upon older siblings' experience with completing the complex application for aid is associated with higher probabilities to claim. Moreover, we find robust evidence that significantly more students socialized in the former socialist East Germany choose to take up student aid than similar West German students. Finally, in line with behavioral economic theory, debt aversion of highly impulsive and impatient students is associated with higher rates of non-take-up.
Keywords: I22; I23; I24; I38; 330; non-take-up of social benefits; welfare program participation; federal student aid; student loans; microsimulation; behavioral economics; debt aversion; self-control